2021
DOI: 10.3390/ijms22157821
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Physical, Microbiological and Immune Barriers of Oral Mucosa

Abstract: The oral mucosa, which is the lining tissue of the oral cavity, is a gateway to the body and it offers first-line protection against potential pathogens, exogenous chemicals, airborne allergens, etc. by means of its physical and microbiological-immune barrier functions. For this reason, oral mucosa is considered as a mirror to the health of the individual as well as a guard or early warning system. It is organized in two main components: a physical barrier, which consists of stratified epithelial cells and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
89
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 94 publications
0
89
0
2
Order By: Relevance
“…The enrichment of these proteins in the S/SEVs from patients with OSCC_LNM could be indicative of dysbiotic signatures occurring during tumor progression. Evidence accumulated in the last years indicates that alterations of the oral microbiome can have a role in inducing oral cancer progression [49][50][51][52]. Interestingly, some of these proteins (as S100 proteins and LCN2) are described as diagnostic and prognostic markers for several types of tumors, even though their role in oral cancer is controversial [48,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of these proteins in the S/SEVs from patients with OSCC_LNM could be indicative of dysbiotic signatures occurring during tumor progression. Evidence accumulated in the last years indicates that alterations of the oral microbiome can have a role in inducing oral cancer progression [49][50][51][52]. Interestingly, some of these proteins (as S100 proteins and LCN2) are described as diagnostic and prognostic markers for several types of tumors, even though their role in oral cancer is controversial [48,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The oral mucosal epithelium is a selective protective barrier that prevents the translocation of periodontal pathogens into gingival connective tissues [ 8 , 9 ]. In a previous investigation, we showed that the cocoa extract used in the present study can improve the barrier function of an oral keratinocyte model by increasing TEER.…”
Section: Discussionmentioning
confidence: 99%
“…The oral mucosa is the first line of defense of the periodontium and acts as a barrier to protect the deeper periodontal connective tissues against bacterial invasion and toxin penetration [ 8 , 9 ]. This protective function is provided by specialized intercellular tight junction proteins that seal the paracellular space between closely opposed cells and govern the permeability of the epithelial barrier [ 8 , 9 ]. However, some periodontal pathogens such as P. gingivalis have evolved effective strategies to counteract the protective function of the epithelial barrier [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The good accessibility and non-traumatic reproduction of the collection of such cells relative to the oral mucosa, as well as the simplicity and low cost of sample preparation, makes them a convenient biological material for in vivo diagnostics of most socially signi cant diseases [4,5]. These cells are highly informative regarding to the in uence of various physical, mechanical, chemical, environmental factors and drugs on the human body [6,7]. The surfaces of the oral mucosa play a signi cant role in the sensory formation of touch, smell and taste, which is largely re ected in the psychoemotional state of a person [8].…”
Section: Introductionmentioning
confidence: 99%